Infusing Engineering Interest: The Effect of “Electronics Topic i-THINK Module” toward Secondary Schools Students’ Achievement - Ridzuan Hashim, Nurulwahida Azid, Fadzilah Amzah (International Journal of Advanced Science and Technology, 2020)
The electronics topic is part of the topics that introduces the basics of engineering to lower secondary students in Malaysia. This study aimed to test the effectiveness of using the i-THINK eight thinking maps module for the electronics topic. The quasi-experimental design through a mixed-method approach was used in this study. A quantitative approach was used to see the mean difference in student achievement scores between the control and treatment groups through pre and post-test. A qualitative approach was applied to look at teachers’ and students’ perceptions through interviews. The study sample consisted of 58 students from two boarding schools consisting of 28 students in the control group and 30 students in the treatment group. Interviews were conducted with two teachers and five students in the treatment group. The instruments used were a set of restricted essay test for pre and post test and interview protocols. Data were analyzed using ANCOVA test analysis and interview data were transcribed and content analysis conducted to identify specific themes. The results showed that there was a significant difference between the control and treatment groups [F (1, 55) = 34.33, p <.05]. The findings from the teacher interview found that the use of the i-THINK map module for electronics topic has stimulated higher order thinking skills, student-centered learning, and enhanced a collaborative work culture through group work. In conclusion, the i-THINK map module has a positive impact on teaching and learning such as stimulating higher order thinking skills, fostering self-learning and enhancing 21st century learning skills and competencies.